2022
DOI: 10.3390/cells11091549
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelet-Rich Plasma Facilitates Angiogenesis to Restore Impaired Uterine Environments with Asherman’s Syndrome for Embryo Implantation and Following Pregnancy in Mice

Abstract: Asherman’s syndrome (AS) is caused by intrauterine adhesions and inactive endometrium from repeated curettage of the uterine endometrium. AS is a major cause of recurrent implantation failure and miscarriage and is very difficult to treat because of the poor recovery of endometrial basal cells. Platelet-rich plasma (PRP) has abundant growth factors that may induce angiogenesis and cell proliferation. Here, we demonstrate that human PRP (hPRP) significantly enhances angiogenesis to restore embryo implantation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
1
8
0
2
Order By: Relevance
“…A few studies have described the beneficial effect of adult PRP ( Kim et al , 2020 , 2022 ; Zhou et al , 2020 ) and commercialized hUC plasma ( de Miguel-Gómez et al. , 2021a ) in preclinical murine models of AS/EA, and have they reported findings similar to the ones presented herein, in terms of endometrial regeneration, augmented angiogenesis, cell proliferation and ability to achieve pregnancy.…”
Section: Discussionsupporting
confidence: 67%
“…A few studies have described the beneficial effect of adult PRP ( Kim et al , 2020 , 2022 ; Zhou et al , 2020 ) and commercialized hUC plasma ( de Miguel-Gómez et al. , 2021a ) in preclinical murine models of AS/EA, and have they reported findings similar to the ones presented herein, in terms of endometrial regeneration, augmented angiogenesis, cell proliferation and ability to achieve pregnancy.…”
Section: Discussionsupporting
confidence: 67%
“…The release of platelet-derived growth factors, vascular endothelial growth factors, transforming growth factors, and epidermal growth factors from activated platelets results in angiogenesis, cell proliferation, differentiation, and modification of the local immune response ( 238 241 ). It can also promote the expression of tissue remodeling genes and reduce fibrosis in mice with Asherman’s syndrome ( 242 ). It has been reported that PRP can improve clinical pregnancy rates and endometrium thickness in patients with RIF ( 231 ).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma has also been studied for regeneration of the endometrium in animal models. [95][96][97] Finally, platelet-derived exosomes may play a regenerating role in the endometrium. A recent report suggests cell proliferation and wound healing in in vitro human endometrial cell lines when exposed to platelet-derived exsosomes.…”
Section: Endometrial Regeneration and Use Of Innovative Therapeuticsmentioning
confidence: 99%